Rheological and physical properties of Inulin-containing milk chocolate prepared at different process conditions - Konar, Nevzat; Ozhan, Bilge; Artik, Nevzat; Dalabasmaz, Sevim; Poyrazoglu, Ender S. (Cyta-Journal of Food, 2014)
In the present study, the effects of inulin as a prebiotic substance at various levels (PSL) (0, 60, 90 and 120 g/kg) in milk chocolate, as well as the use of varying conching time (CT) (3.50, 4.0 and 4.50 h) and refining conditions (20.0, 25.0 and 28.0 μm as the mean particle size, D[4,3]) in the sample preparation process were examined with respect to changes in the physical (colour, hardness, water activity) and rheological properties of the samples. Specific surface area (SSA) and largest particle size (D90) values increased with increasing values of PSL; however, intended D [4,3] values were reached for all PSL values. CT, PSL and PSD (particle size distribution) had no significant effect on the brightness and chroma in the inulin-containing milk chocolate; however, it has been found that hardness, water activity, yield stress and viscosity produced significant changes (P < 0.01). © 2013 © Taylor & Francis.
Created from Fastlane, Scopus look-up
Keywords: chocolate; conching; inulin; particle size distribution; prebiotic